Agricultural Social Capital: Study of Trust and Reciprocity in Tanah Towa Village, Bulukumba Regency - Nur Indah Sari Basir; Andi Muh. Akbar Alamsyah; Firmayanti Muslimin (Newinera Publisher, 2020)
The purpose of this study was to determine the Agricultural Social Capital, especially the elements of trust and reciprocity in Tanah Towa Village, Bulukumba Regency. The research method used is qualitative with interviews and discussion data collection techniques. The results of this study indicate that social capital in Tanah Towa villagers can be seen from the trust, cooperation and networks, collective action, reciprocal relationships (reciprocity), which occur in the community. And based on the overall results obtained by the trust of the village community quite well, cooperation such as farmer groups and farmer groups combined and reciprocal relationships with the community not only occur in close relatives but on all communities depending on the level of closeness between individuals social capital is a big thing in the development and progress of human resources for the development of a nation.